Logistics Administration cost Analysis in Food Industry - Sea-Sio, Bunchai (Journal of Advanced Development in Engineering and Science, 2023)
The objective of this research to study and compare logistics costs calculation concepts in Thai industries from 30 small enterprises, 30medium enterprises, and 30 big enterprises in order to collect data and compare logistics costs in administrations (CAdmins) according to CASS Method that analyze administrations cost (CAdmins) at 10% of the total expenses from transportation cost (CTran) and inventory carrying cost (CInvent) and data from the industrial logistics performance indicators including ILPI1C: Forecasting Cost per Sales (CILPI1), ILPI2C: Customer Service Cost per Sales (CILPI2), ILPI3C: Information Processing Cost per Sales (CILPI3), ILPI4C: Procurement Cost per Sales (CILPI4), ILPI5C: Damage Value per Sales (CILPI5), and ILPI9C: Returned Goods Cost per Sales (CILPI9). The study results showed that the administration cost (CAdmins) of small and medium enterprises using data from the industrial logistics performance indicators was higher than CASS Method. The administrations cost (CAdmins) of small enterprises was at 29,794,124.16 baht and was 5.50% of the sales while the administrations cost (CAdmins) from the CASS Method was at 5,950,500.35 baht and was at 1.10% of the sales. The administrations cost (CAdmins) of medium enterprises was at 188,532,364.72 baht and was 3.49% of the sales while the administrations cost (CAdmins) from the CASS Method was at 52,989,890.95 baht and was at 0.98% of the sales. At the same time, the administrations cost (CAdmins) of big enterprises from the industrial logistics performance indicators was lesser than the CASS Method and was at 318,171,359.82 baht and was 1.39% of the sales while the administrations cost (CAdmins) from the CASS Method was at 138,822,298.37 baht and was at 0.61% of the sales. The results of the study showed that a factor that caused high administrations costs (CAdmins) in small and medium enterprises was because of the lack of integrating technologies or information systems in the business or it may be caused by the development period of these enterprises as well.